Implementation of Gifted Children Education Services from the Middle School to Higher Education - Dwi Agies Yuliany; Tjutju Soendari (Journal of ICSAR, 2019)
Gifted children need special services at school and college, especially in developments that include cognitive, physical, language, emotional, social and academic aspects. Currently there are educational services that can facilitate them in the form of SKS (Semester Credit System) programs. One of the schools that organizes SKS is SMAN 3 Bandung. The purpose of SKS learning is to provide the flexibility for students to learn and grow according to their abilities, talents and interests, in addition to fulfilling the applicable policies. In general, the implementation of SKS is divided into three main stages, including 1) preparation, 2) implementation, and 3) monitoring and evaluation. For fast learners, enrichment program services are provided so that they can complete the entire learning program faster than the quota in high school which is six semesters. This is very useful for students who have the giftedness so that they can complete in just 4 (four) semesters, but the report books they receive remain 6 (six) semesters. As a follow-up at the University there is a fast track program at Bandung Institute of Technology where Undergraduate students who are at their final semester can attend Master program. The main objective of this program is to accelerate students in completing studies. Fast track students are those who can complete their bachelor and master degree in 5 years. This SKS and Fast Track program is one of the services that can be used for gifted children because it is very effective and efficient in completing their education faster.